The Rural Blended Learning Strategy for the teaching of Physical Sciences in Rural schools: Rural Blended Learning Strategy - Tebogo Edwin Nkanyani (Studies in Learning and Teaching, 2026)
This paper designed a blended learning strategy for teaching Physical Sciences in rural schools. It followed a social constructivism approach since it is embedded in learners' engagement in a co-operative manner with the Analyze, Design, Develop, Implement, and Evaluate model key in the strategy design, inspired by the flipped classroom model. The study ensued through a qualitative approach to research, using semi-structured interviews together with both classroom and field observations. A purposeful sampling strategy was employed, and the participants were from a rural area. The findings reveal that the sampled school suffers from network issues, which are compounded by loadshedding, long distances to Wi-Fi centers, and poor institutional support for learners, among others. However, the school provides good institutional support to teachers, has exposure to social media learning, and contains a number of devices. The paper concludes by proposing the Rural Blended Learning Strategy to be used in Physical Sciences classrooms in rural schools, together with its practical implications.